Deathless divide - Ireland, Justina (Balzer + Bray, an imprint of HarperCollinsPublishers, 2020)
The sequel to the New York Times bestselling epic Dread Nation is an unforgettable journey of revenge and salvation across a divided America. After the fall of Summerland, Jane McKeene hoped her life would get simpler: Get out of town, stay alive, and head west to California to find her mother. But nothing is easy when you're a girl trained in putting down the restless dead, and a devastating loss on the road to a protected village called Nicodemus has Jane questioning everything she thought she knew about surviving in 1880s America. What's more, this safe haven is not what it appears--as Jane discovers when she sees familiar faces from Summerland amid this new society. Caught between mysteries and lies, the undead, and her own inner demons, Jane soon finds herself on a dark path of blood and violence that threatens to consume her. But she won't be in it alone. Katherine Deveraux never expected to be allied with Jane McKeene. But after the hell she has endured, she knows friends are hard to come by--and that Jane needs her too, whether Jane wants to admit it or not. Watching Jane's back, however, is more than she bargained for, and when they both reach a breaking point, it's up to Katherine to keep hope alive--even as she begins to fear that there is no happily-ever-after for girls like her
Sequel to: Dread Nation
Keywords: Bodyguards / Fiction; Zombies / Fiction; African Americans / Fiction; Young women / Fiction; Friendship / Fiction; Racism / West (U.S.) / Fiction; West (U.S.) / History / 19th century / Fiction; West (U.S.) / Race relations / Fiction; Horror stories; YOUNG ADULT FICTION / Action & Adventure / Survival Stories; YOUNG ADULT FICTION / Historical / United States / Civil War Period (1850-1877); YOUNG ADULT FICTION / People & Places / United States / African American; African Americans; Bodyguards; Friendship; Race relations; Racism; Young women; Zombies; West United States; Zombies / Juvenile fiction; African Americans / Juvenile fiction; 1800-1899; Young adult fiction; Historical Fiction; Juvenile works; Action and adventure fiction; Alternative histories (Fiction); Fantasy fiction; Fiction; History; Horror fiction; Young adult works; Jugendbuch